PENGARUH HARGA, KUALITAS PRODUK, KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MAKANAN CEPAT SAJI KAREN’S DINER (Studi Kasus Pada Pelanggan Karen’s Diner Jakarta Selatan) - Dina Safitri; Fenny B.N.L. Tobing; Christina Natalina (Universitas Kristen Indonesia, 2023)
Purposes of these studies was to assess effect of prices, product qualities, and service qualities on purchasing decision. South Jakarta Karen's Diner fast food. To obtain data for this research study by give questionnaire to respondent who already have a criteria, have used the product, the same community as the research object. Karen's diner fast food customers are the population of these studies, number of samples that have answered the research questionnaire is 50 respondents. Price, product quality, service quality are independent variable and dependent variable in these studies is purchasing decision. The result of these studies shows that prices, product qualities, service qualities and purchasing decisions at Karen's diner are quite good. There is an effect of prices on decisions to purchase karen's diner fast food with a sig value of 0.001, there is an influences of product qualities on decision to purchase fast food karen's diner with a sig value of 0.000 and there are no effects of service qualities on decision to purchase fast food karen's diner with a significancy value of 0.731. Keywords: Prices, Product Quality, Service Qualities, Purchase Decision